2019
DOI: 10.3233/jbr-180329
|View full text |Cite
|
Sign up to set email alerts
|

Physiological response and susceptibility of strawberry cultivars to the charcoal rot caused by Macrophomina phaseolina under drought stress conditions

Abstract: BACKGROUND: Charcoal rot of strawberry (Macrophomina phaseolina) is an emerging disease difficult to manage, a desirable alternative is the use of resistant cultivars. However, little is known regarding the reaction of cultivars to the pathogen under water stress conditions. OBJECTIVE: The aims of this work were to study the effect of water stress on the physiology of four strawberry cultivars during the infection, and to determine the relationship between water stress and cultivar susceptibility. METHODS: Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Infection caused by species from the genus Macrophomina mainly affects roots, limiting water and nutrient uptake by plants, consequently impairing their development (Sánchez et al, 2019). Such behavior was observed in both melon types studied, with an intense reduction in length and fresh weight on this organ.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Infection caused by species from the genus Macrophomina mainly affects roots, limiting water and nutrient uptake by plants, consequently impairing their development (Sánchez et al, 2019). Such behavior was observed in both melon types studied, with an intense reduction in length and fresh weight on this organ.…”
Section: Discussionmentioning
confidence: 82%
“…Similarly, Purkayastha et al (2006) observed that some genetically distinct M. phaseolina isolates were more aggressive to cluster bean. Moreover, high genetic diversity in the genus Macrophomina can reflect on its degree of pathogenicity since changes in their physiological characteristics guarantee adaptability to different agroecological conditions (Sánchez et al, 2019;Rafiei et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…An appearance of powdery black sclerotia is found under the epidermis and root at the seed formation stage in the infected plants. Sometimes, the plant symptoms of this disease are confused with other plant abiotic stresses like drought or abiotic stress like cyst nematode, therefore the detection of this disease based on morphological aerial plant parts is challenging ( Sanchez et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…This is particularly evident in cases where pathogens colonise the plant's vascular system, block the xylem, and disrupt normal water transport, exacerbating the negative effects of water deficit. For example, strawberry plants infected with M. phaseolina exhibit relatively lower stem (xylem) water potential and stomatal conductance under drought stress (Sánchez et al, 2019). When re-irrigated, infected plants cannot recover, while uninfected plants subjected to drought stress do.…”
Section: Plant Genotypementioning
confidence: 99%